Typology Of Cattle Herds In Transhumance In The Classified Forest Of Upper Alibori Northern Benin - ASSANI SEIDOU, Alassan; ALKOIRET TRAORE, Ibrahim; HOUINATO, MARCEL ROMUALD BENJAMIN; MENSAH, GUY APOLLINAIRE (My University, 2016)
To characterize the cattle herds in transhumance in the classified forest of upper Alibori (CFUA) north of Benin, an investigation of 132 cattle herds with a total of 11,020 head was carried out. Using the methods of factorial analysis of multiple correspondences (FAMC) and ascending hierarchical classification (AHC), a typology of four types of transhumant cattle herds were established. Cattle herds of type 1 (17.5% of the sample) were riparian of CFUA. They were led by young herdsmen (17 ± 3 years), all parents of herds’ managers to whom they use to make all decisions concerning these herds whose average size is low (44 ± 20 head). Type 2 cattle herds (28.8% of the sample) were from the neighboring commons of CFUA and were led by two relatively young herdsmen (26 ± 3 years) and mostly parents of herds’ managers with which they conferred to make decisions. These herds had an average size of 94 ± 20 head. The third type (43.9% of the sample) consisted of transhumant herds from distant commons, passing through the CFUA towards other protected areas. They had a high size (112 ± 13 head) and were conducted by two relatively young herdsmen (31 ± 4 years) and mostly parents of herds’ managers. Decisions were taken by the herds’ managers sometimes in consultation with the herdsmen. The migratory herds of type 4 (9.8% of the sample) from neighboring countries. They went through the CFUA towards protected areas further south with a very high size (144 ± 15 head). These herds were conducted generally by two or three herdsmen whose average age was 36 ± 4years and were heavily involved in decision making in consultation with the herds’ managers. The typology implementation will allow us to analyze the different transhumance management modes in the CFUA.
Keywords: Benin; cattle herd; protected area; transhumance; typology